1997
DOI: 10.1017/s0033291796004254
|View full text |Cite
|
Sign up to set email alerts
|

Social support and psychiatric sickness absence: a prospective study of British civil servants

Abstract: Negative aspects of close relationships may have an aetiological role in non-psychotic psychiatric disorder. Social support at work appears to protect against short spells of psychiatric sickness absence. This potentially implies that levels of short spells of absence might be reduced by increasing support at work. Conversely, emotional support at home may influenced absence-related behaviour and encourage a person to take absence at a time of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 29 publications
5
94
1
5
Order By: Relevance
“…They can have both a negative and positive effect on employee productivity, health and well-being [see 5 for a review]. For example, supervisor support is associated with increased productivity [6], lower sickness absence [7], a decrease in risk for future depression [8] and lower turnover intentions [9]. Conversely, poor manager-employee relationships and lack of line manager support is reported as a common source of stress and low well-being among employees [5,10].…”
Section: The Influence Of Line Managers On Employee Health and Well-bmentioning
confidence: 99%
“…They can have both a negative and positive effect on employee productivity, health and well-being [see 5 for a review]. For example, supervisor support is associated with increased productivity [6], lower sickness absence [7], a decrease in risk for future depression [8] and lower turnover intentions [9]. Conversely, poor manager-employee relationships and lack of line manager support is reported as a common source of stress and low well-being among employees [5,10].…”
Section: The Influence Of Line Managers On Employee Health and Well-bmentioning
confidence: 99%
“…In a systematic review, it was shown that positive leader behaviours (such as support and empowerment) are associated with a low degree of employee stress. [9] Supervisor support is associated with increased productivity, [10] and with lower sickness absence, [11] whereas low supervisor support is associated with increased long-term sick leave. [12] In addition to permanent work disability and sick leave, at-work productivity is often impacted by RA.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness is associated with higher functioning in the executive control processes [5], correlated with less atrophy of frontal cortex regions [6], and with improved reaction times [7] compared with the sedentary. Social interaction, and specifically high perceived interpersonal social support, has also been shown to have a positive impact on general mental and physical wellbeing [12], in addition to reducing the likelihood of depression [13]- [16]. Among the many healthcare services that will need to be provided, physical exercise therapy, social interaction, and companionship can be addressed by socially assistive robotics technology.…”
Section: Introductionmentioning
confidence: 99%